The impact of bonus issue announcements on the stock prices and its volatility in Malaysia / Nor Diyani Adnan - Adnan, Nor Diyani (Faculty of Business and Management, 2007)
This study is conducted to see the impact of bonus issue announcements on the stock prices and its volatility in Malaysia during year 2003. An event study analysis is used to investigate stock prices reaction to the announcement of bonus issues in Malaysia. This research covers stock prices ten days before and after the bonus issue announcements in order to analyze stock price's volatility. On the other hand, the impact of bonus issue announcement can be measure using average return of the stock and market. From the findings, only ten percent from the chosen companies have more volatile stock prices and other ninety percent are less volatile. Based on the average return graph, it shows a positive abnormal return which means the announcement of bonus issue give positive impact to the stock prices. As a conclusion, the stock prices can be said less volatile regarding to the bonus issue announcement. On the other side, bonus issue announcement give positive impact to the stock prices in Malaysia.